2021
DOI: 10.1136/jim-2021-001810
|View full text |Cite
|
Sign up to set email alerts
|

Hemogram as Marker of In-Hospital Mortality in Covid-19

Abstract: The clinical impact of COVID-19 disease calls for the identification of routine variables to identify patients at increased risk of death. Current understanding of moderate-to-severe COVID-19 pathophysiology points toward an underlying cytokine release driving a hyperinflammatory and procoagulant state. In this scenario, white blood cells and platelets play a direct role as effectors of such inflammation and thrombotic response. We investigate whether hemogram-derived ratios such as neutrophil-to-lymphocyte ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 27 publications
(70 reference statements)
5
36
0
2
Order By: Relevance
“…NLR displayed a disproportion of the inflammatory response in COVID-19 patients, and some studies found that high NLR is independently related with disease severity and mortality [ 33 , 34 ]. Also, serial NLR measurements in hospitalized patient with COVID-19 is a good predictor for mortality, as well as, some studies found that increase in NLR is associated with mortality [ [35] , [36] , [37] , [38] , [39] ]. Our findings showed that high dose melatonin significantly reduced NLR when added to standard treatment and ultimately decline mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR displayed a disproportion of the inflammatory response in COVID-19 patients, and some studies found that high NLR is independently related with disease severity and mortality [ 33 , 34 ]. Also, serial NLR measurements in hospitalized patient with COVID-19 is a good predictor for mortality, as well as, some studies found that increase in NLR is associated with mortality [ [35] , [36] , [37] , [38] , [39] ]. Our findings showed that high dose melatonin significantly reduced NLR when added to standard treatment and ultimately decline mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets and neutrophils had important effects on the thrombo-inflammatory phase of COVID-19 [ 35 ]. Studies have confirmed that lower total platelets count and decrease in platelets was detected in severe COVID-19 cases and non-survived group [ 35 , 36 ]. Our study showed that there is a significant difference between the two groups in terms of platelet depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Lung fibrosis observed in COVID‐19 patients and resulting hypoxia is the main reason for mortality in severe cases which can also be complicated by secondary bacterial and fungal infections 77 . COVID‐19 infection in humans is primarily asymptomatic or exhibiting a mild disease unless it manifests with the onset of hypoxemia from pneumonitis which may progress to ARDS with similarities to toxic shock syndrome (TSS) 78 . There is still a lack of understanding as to why some individuals are asymptomatic, some require low‐oxygen supplementation to then recover, while others rapidly decompensate into ARDS 79 .…”
Section: Protein Modeling Protein–protein Docking and MD Simulationsmentioning
confidence: 99%
“…77 COVID-19 infection in humans is primarily asymptomatic or exhibiting a mild disease unless it manifests with the onset of hypoxemia from pneumonitis which may progress to ARDS with similarities to toxic shock syndrome (TSS). 78 There is still a lack of understanding as to why some individuals are asymptomatic, some require low-oxygen supplementation to then recover, while others rapidly decompensate into ARDS. 79 It is possible that once a threshold is crossed by either uncontrolled hyperinflammation Both Hepcidin and Covidin bind strongly to the central pore from the extracellular space of a host iron transporter "ferroportin" and the resulting complex has similar interaction features and binding space as the natural hormone Hepcidin and/or stimulation of the signaling pathways comodulated by hypoxia and the result is ARDS.…”
Section: Relationship Of Iron Transport Hepcidin and Covidinmentioning
confidence: 99%
“…Although more research is needed, one of the markers that can predict the correct mortality rate among COVID-19 ICU patients is mid-regional pro-adrenomedullin (MR-proADM): it presented as high levels in non-survivors (113). In addition, several recent studies have shown new markers such as neutrophil-to-lymphocyte ratio, neutrophil-to-platelet ratio, uric acid level, total antioxidant capacity, eosinophil/PMN ratio, high-density lipoprotein, and apoprotein A1 (114)(115)(116)(117)(118)(119).…”
Section: M-mdsc In Covid-19mentioning
confidence: 99%